Immunohistochemical evaluation of acyl-CoA synthetase long-chain family member 4 (ACSL4) immunoreactivity in malignant melanoma specimens - Celik, Mehmet Semih; Asir, Firat; Aktas, Hamza; Cetin, Alpay; Celik, Candan; Cepik, Nagehan; Karakoyun, Omer (Springer, 2026)
Acyl-CoA synthetase long-chain family member 4 (ACSL4) is a lipid-metabolizing enzyme implicated in ferroptosis regulation and tumor aggressiveness. Although ACSL4 overexpression has been reported in various malignancies, its immunohistochemical profile in primary cutaneous melanoma has not been fully characterized. This study aimed to evaluate ACSL4 expression in melanoma compared with normal skin using quantitative digital image analysis. A total of 80 formalin-fixed paraffin-embedded samples were analyzed, including 50 primary cutaneous melanoma specimens and 30 control skin samples obtained from benign dermatologic excisions. Hematoxylin-eosin staining was used to assess histopathologic features, and ACSL4 immunostaining was performed using a standardized protocol. Quantitative evaluation was conducted with QuPath software by calculating the percentage of positive cells, mean intensity scores (0-3), and H-scores (0-300) in epidermal and dermal compartments. Group comparisons were performed using the independent t test, with p < 0.05 considered statistically significant. Control tissues exhibited minimal ACSL4 expression (epidermal H-score 12; dermal H-score 9), whereas melanoma specimens demonstrated markedly increased ACSL4 immunoreactivity. Dermal atypical melanocytic tumor cells showed the highest expression levels (mean intensity 2.10 +/- 0.35; H-score 168; p < 0.001), while epidermal layers also exhibited moderately elevated staining (H-score 58; p < 0.001). Histopathologic evaluation revealed characteristic features of invasive melanoma, including atypical melanocytic nests, pagetoid spread, cytologic atypia, and architectural disorder. Overall, ACSL4 expression was significantly upregulated in primary cutaneous melanoma compared with normal skin, particularly within dermal atypical melanocytic tumor cells, suggesting that ACSL4 may contribute to melanoma biology through lipid metabolic pathways and may represent a potential biomarker of tumor aggressiveness, warranting further investigation into its diagnostic and prognostic relevance.
Keywords: ACSL4; Melanoma; Immunohistochemistry; QuPath; Lipid metabolism; Ferroptosis; Skin tumors; Biomarker